2014
DOI: 10.1371/journal.pone.0091751
|View full text |Cite
|
Sign up to set email alerts
|

Utility of R2* Obtained from T2*-Weighted Imaging in Differentiating Hepatocellular Carcinomas from Cavernous Hemangiomas of the Liver

Abstract: PurposeTo evaluate the feasibility of applying R2* values to differentiate hepatocellular carcinomas (HCC) from cavernous hemangiomas of the liver (CHL).Materials and MethodsThis retrospective study was approved by the participating Institutional Review Board and written informed consent for all subjects were obtained. Seventy-three patients with 79 pathologically identified HCCs and 65 patients with 91 clinically or pathologically identified CHLs were enrolled in this study. All subjects underwent a breath-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In contrast, in the nonresponder group tumor hypoxia might increase, which results in the higher deoxyhaemoglobin concentration and thus R2* value increases. 26 The area under the ROC of R2* was 0.769. The sensitivity was 78.3%, and specificity was 67.6% when the cutoff value was set as 28.37 Hz, which implicates that R2* might be helpful for discriminating responders from nonresponders.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, in the nonresponder group tumor hypoxia might increase, which results in the higher deoxyhaemoglobin concentration and thus R2* value increases. 26 The area under the ROC of R2* was 0.769. The sensitivity was 78.3%, and specificity was 67.6% when the cutoff value was set as 28.37 Hz, which implicates that R2* might be helpful for discriminating responders from nonresponders.…”
Section: Discussionmentioning
confidence: 95%
“…The possible reason is that the responder group might have good tumor oxygenation, which results in lower deoxyhaemoglobin concentration and thus R2* value decreases. In contrast, in the nonresponder group tumor hypoxia might increase, which results in the higher deoxyhaemoglobin concentration and thus R2* value increases . The area under the ROC of R2* was 0.769.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [26] reported that magnetic resonance blood oxygen level parameters R2 * and T2 * and their associated measurements were correlated with the clinical and 7 Computational and Mathematical Methods in Medicine pathological features of HCC. Zhang et al [27] investigated the significance of mean platelet volume (MPV) in discriminating HCC from ICCA and found that MPV correlation discrimination had the AUC, sensitivity, and specificity of 0.698, 80.2%, and 54.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…23 In the process of IONs modication, SC is employed as stabilizer in the aer-treatment of IONs obtained by hydrothermal method, thermal decomposition method and co-precipitation method. 24,25 Polyethylenimine (PEI) coated IONs were synthesized through co-precipitation and modied by SC and PEI, which was used in the absorption for hexavalent chromium. 26 This work provided a simple and one pot method for synthesizing IONs with different sizes by adding different concentrations of SC.…”
Section: Introductionmentioning
confidence: 99%